Caucasian Albania An International Handbook - Gippert, Jost; Dum-Tragut, Jasmine (De Gruyter Reference, 2023)
The handbook illustrates the present state of knowledge on the region of Albania in the Southern Caucasus and its inhabitants with a focus on its late antique and medieval history, its language and its written heritage, its religion and its architecture, commonly authored by a group of international experts. Particular attention is directed to the relationship of the Caucasian Albanians with neighbouring peoples and its development over time.